Collection and direct amplification methods using the GlobalFiler™ kit for DNA recovered from common pipe bomb substrates. Issue 5 (September 2019) - Tasker, Esiri; Mayes, Carrie; LaRue, Bobby; Hughes-Stamm, Sheree
Abstract: When analyzing DNA from exploded pipe bombs, quantities are often in trace amounts, making DNA typing extremely difficult. Amplifying minute amounts of DNA can cause stochastic effects resulting in partial or uninterpretable profiles. Therefore, the initial DNA collection from "touch" evidence must be optimized to maximize the amount of DNA available for analysis. This proof-of-concept study evaluated two different swab types with two direct amplification strategies to identify the most effective method for recovering DNA from common pipe bomb substrates. PVC and steel pipes, electrical tape, and copper wire spiked with epithelial cells were swabbed with cotton or microFLOQ® Direct Swabs and amplified directly or via a pre-treatment prior to STR amplification. Not only was the microFLOQ® Direct Swab protocol the quickest method with the least risk of contamination, but in combination with direct amplification, the microFLOQ® Direct Swabs also generated the most complete STR profiles. Highlights: Sufficient DNA loss was observed during traditional DNA extraction on an automated platform. More complete STR profiles were observed when microFLOQ® Direct Swabs were amplified directly. More DNA was recovered from electrical tape regardless of the processing method used.